Analisis Kepuasan Pegawai Atas Kepemimpinan - Anwar, Samsul (Perhimpunan Sarjana Ekonomi dan Bisnis, 2023)
Employee satisfaction is an important factor in maintaining productivity, loyalty and overall organizational performance. One of the factors that has a big influence on employee satisfaction is the leadership in the organization. Effective leadership is able to motivate, guide, and provide support to employees. Therefore, this study aims to analyze the level of employee satisfaction with leadership in an organization. The main objective of this study is to analyze the level of employee satisfaction with leadership in the organization. This study also aims to identify the factors that influence employee satisfaction with leadership, as well as evaluate the impact of employee satisfaction on their performance and loyalty. The research method used in this study is a quantitative survey method. Data was collected by distributing questionnaires to all employees in the organization that was the subject of the study. The questionnaire is designed to measure the level of employee satisfaction with leadership, as well as collect information about the factors that influence this satisfaction. Data analysis was performed using various statistical techniques, including path analysis to identify the influence between variables. The results of this study indicate that most employees in the organization have a high level of satisfaction with leadership. Factors such as effective communication, support from superiors, and recognition for employee contributions have a significant positive impact on employee satisfaction. In addition, employee satisfaction has also been shown to have a positive correlation with their performance in the organization and a high level of loyalty. This shows the important role of effective leadership in creating a work environment that motivates and meets the needs of employees.